Monthly CERA Treatment Maintains Stable Hemoglobin Levels in Routine Clinical Practice of Peritoneal Dialysis Patients. (April 2013) - González, Ma Teresa; Ramos, Rosa; Vera, Manel; Barbosa, Francesc; Garcia, Carmen; Garcia, Isabel; González-Segura, Carlota; Cuxart, Marc; Teixidó, Josep; Cruz, Juan José de la
<x xml:space="preserve">Abstract</x> Data on routine use of continuous erythropoietin receptor activator (CERA) in peritoneal dialysis patients are scarce. This study aimed to assess the efficacy of CERA administered once monthly in maintaining stable Hb levels in patients on peritoneal dialysis under routine medical practice. This was a 12-month, observational, prospective and multicenter study. A total of 83 patients with anemia secondary to chronic kidney disease (CKD) on peritoneal dialysis for more than 3 months, on once-monthly subcutaneous CERA treatment, were followed up over a period of 1 year. Efficacy evaluation included Hb levels, mean time in which the Hb level was maintained within target range, CERA doses and number of dose changes. Median Hb level (interquartile range [IQR]) remained stable during the evaluation period [11.8 ± 1.4 g/dL at baseline, 11.8 ± 1.4 g/dL at month 6 and 11.8 ± 1.5 g/dL at month 12 (p > 0.05)]. The median (IQR) time of Hb level maintained within target range (11–13 mg/dL) was 6 (4–10) months. Ferritin, transferrin saturation index, and Fe were also stable and well maintained during the 12 months (p > 0.05). CERA mean dose (SD) was [115.4 (56.2) μg baseline; 117.2 (58.5) μg 6 months; 126.0 (65.9) μg 12 months (p = 0.127)]. The mean number of CERA dose changes per patient during the study was 1.6 (SD 1.3). Serious adverse events were not related to CERA treatment. The results suggest that once-monthly CERA successfully corrects anemia and maintains stable Hb levels within the recommended target range on peritoneal dialysis under routine medical practice.